2019
DOI: 10.1101/815621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving cell distribution on 3D additive manufactured scaffolds through engineered seeding media density and viscosity

Abstract: In order to ensure the long-term in vitro and in vivo functionality of cell-seeded 3D scaffolds, an effective and reliable method to control cell seeding efficiency and distribution is crucial. Static seeding on 3D additive manufactured scaffolds made of synthetic polymers still remains challenging, as it often results in poor cell attachment, high cell sedimentation and non-uniform cell distribution, due to gravity and to the intrinsic macroporosity and surface chemical properties of the scaffolds. In this st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Previously, it has been shown that cell distribution and density upon seeding can significantly influence hMSCs osteogenic differentiation in 3D scaffolds. [42, 58, 59] Accordingly, poor cell attachment and lack of confluency within the scaffold cross-section have been shown to result in poor differentiation and lack of matrix mineralization in vitro. Besides, some studies reported enhanced cell attachment on polymer-CaP composites, likely due to the hydrophilicity and protein adsorption capacity of the CaP [60, 61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been shown that cell distribution and density upon seeding can significantly influence hMSCs osteogenic differentiation in 3D scaffolds. [42, 58, 59] Accordingly, poor cell attachment and lack of confluency within the scaffold cross-section have been shown to result in poor differentiation and lack of matrix mineralization in vitro. Besides, some studies reported enhanced cell attachment on polymer-CaP composites, likely due to the hydrophilicity and protein adsorption capacity of the CaP [60, 61].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in order to decouple the osteogenic potential of the PEOT/PBT-nHA composite scaffolds from the effect of attachment efficiency, a viscous solution was used as seeding media, thereby ensuring comparable cell attachment and homogeneity among all scaffolds regardless of the nHA content, as previously reported. [42] Due to scaffold surface saturation with cells upon seeding, no cell proliferation was observed in the first 7 days of culture, nor during the subsequent 28 days in BM on any scaffold type, as ECM production was limited to the scaffolds filaments surface. On the other hand, ECM was also produced within the pores when cultured in MM, which increased the growth surface area enabling cell migration and a slight, yet not statistically significantly different, increase of cell number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, scaffolds were blotted on top of a sterile filter paper and placed in the wells of a non-treated wellplate. Trypsinized hMSCs were resuspended in a dextran solution (500 kDa, Farmacosmos) (10 wt% dextran in CM), to achieve uniform cell distribution, [33] and were seeded at a density of 2×10 5 cells with 37 μl of CM per scaffold. After 4h incubation for cell attachment, scaffolds were transferred to new wells containing 1.5 ml of basic media (BM) (CM supplemented with 200 μм L-Ascorbic acid 2-phosphate).…”
Section: Methodsmentioning
confidence: 99%
“…Based on Torres et al study result [35], four different densities and related viscosity were assigned to the culture media.…”
Section: Fluid Properties and Boundary Conditions In Cfdmentioning
confidence: 99%